Deterministic and stochastic model for the effect of Chondroitin Sulfate (CS) in cancer cell - Rosli, Norhayati; Ismail, Farhana (Pusat Pengurusan Penyelidikan Dan Inovasi, Universiti Teknikal Malaysia Melaka, 2022)
Modern medical study show that the new therapeutic strategies known as targeted therapy can help in cancer prognoses. Chondroitin Sulfate (CS) an anticancer drug in targeted therapy has been proved able to reduce cell viability by promoting the activation of the Caspase3 (Casp3) in apoptosis pathway without causing toxicity. To better understand the effect of CS on the cancer cells, deterministic and stochastic model are proposed. The result shows the decreasing trend of the cancer cell in the presence of CS in both models.